Establishment of a zebrafish map3k15knockout line using CRISPR/Cas9 gene editing technology - JIA Chunyu, SHEN Yan, CHEN Gang, ZHENG Ke, QIN Yan, LI Xuemei (Jichu yixue yu linchuang)
Objective To establish a homozygous zebrafish map3k15 knockout line using CRISPR/Cas9 gene editing technology so to provide an animal model for investigation of potential role of map3k15 in renal diseases. Methods 1)Analyzing the expression pattern of map3k15 in zebrafish; 2)Establishing a homozygous map3k15 knockout zebrafish line using CRISPR/Cas9; 3)Observing the phenotypic effects of map3k15 deficiency in zebrafish. Results 1)map3k15 was expressed in the zebrafish pronephros, and map3k15/map3k15 protein was found highly conserved across species; 2)map3k15-/- mutant zebrafish model was constructed with +2 bp mutation and +1 bp mutation; 3)map3k15 mutant zebrafish exhibited edema in yolk sac, pericardium and head during embryonic development. Conclusions A homozygous zebrafish map3k15 knockout line is successfully developed which may provide an important model for future research on the role of map3k15 in renal development and disease.